JIKA PENGHARGAAN TIDAK BERPENGARUH PADA KINERJA, MENGAPA HUKUMAN BISA? - Ahmad Nizar Yogatama (Jurnal Manajemen dan Profesional, 2022)
The Malang Regency Land Office is currently dealing with an issue, which is the existence of a number of personnel who are not as vigilant in the performance of their tasks, which has led to the accumulation of infractions. This research was conducted with the intention of determining the impact that monetary rewards and negative consequences have on the overall performance of workers at the Malang Regency Land Office. The personnel of the Malang Regency Land Office makes up both the population and the sample that was used. Methods of data analysis that make use of multiple linear regression. According to the findings of the study, the research shows that a reward does not have a substantial impact on the performance of employees, however, punishment does have a big impact on employee performance.